Profiling of Steroid Metabolic Pathways in Human Plasma by GC-MS/MS Combined with Microwave-Assisted Derivatization for Diagnosis of Gastric Disorders - Lee, Wonwoong; Lee, Hyunjung; Kim, You Lee; Lee, Yong Chan; Chung, Bong Chul; Hong, Jongki (MDPI, 2021)
Steroid hormones are associated in depth to cellular signaling, inflammatory immune responses, and reproductive functions, and their metabolism alterations incur various diseases. In particular, quantitative profiling of steroids in plasma of patients with gastric cancer can provide a vast information to understand development of gastric cancer, since both sex hormones and glucocorticoids might be correlated with the pathological mechanisms of gastric cancer. Here, we developed a gas chromatography-tandem mass spectrometry-dynamic multiple reaction monitoring (GC-MS/MS-dMRM) method combined with solid-phase extraction (SPE) and microwave-assisted derivatization (MAD) to determine 20 endogenous steroids in human plasma. In this study, MAD conditions were optimized with respect to irradiation power and time. The SPE enabled effective cleanup and extraction for profiling of steroid hormones in human plasma samples. The MAD could improve laborious and time-consuming derivatization procedure, since dielectric heating using microwave directly increase molecular energy of reactants by penetrating through medium. Furthermore, dMRM method provided more sensitive determination of 20 steroids, compared to traditional MRM detection. The limits of quantification of steroids were below 1.125 ng/mL and determination coefficients of calibration curves were higher than 0.9925. Overall precision and accuracy results were below 19.93% and within +/- 17.04%, respectively. The developed method provided sufficient detection sensitivities and reliable quantification results. The established method was successfully applied to profile steroid metabolism pathways in plasma of patients with chronic superficial gastritis (CSG), intestinal metaplasia (IM), and gastric cancer. Statistical significances of steroid plasma levels between gastric disorder groups were investigated. In conclusion, this method provided comprehensive profiling of 20 steroids in human plasma samples and will be helpful to discover potential biomarkers for the development of gastric cancer and to further understand metabolic syndrome.